Respostas
respondido por:
4
7^x.7^(-1) + 7^x.7^1 = 50
7^x [7^(-1).7^1] = 50
7^x = 50
7^x = (1 + 49)
7^x = (7^0 + 7^2)
aplica log nos dois lados:
log 7^x = log (7^0 + 7^2)
x.log7 ^x = log(7^0.log7^2)
x.log7 ^x = log7^2
x.log7 ^x = 2.log7
x = 2
7^x [7^(-1).7^1] = 50
7^x = 50
7^x = (1 + 49)
7^x = (7^0 + 7^2)
aplica log nos dois lados:
log 7^x = log (7^0 + 7^2)
x.log7 ^x = log(7^0.log7^2)
x.log7 ^x = log7^2
x.log7 ^x = 2.log7
x = 2
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás